1998
DOI: 10.1212/wnl.51.3_suppl_3.s23
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac evaluation of stroke patients

Abstract: There are two potential purposes for cardiac evaluation in patients with cerebrovascular disease: to identify possible cardioembolic pathophysiology for ischemic symptoms and to identify concomitant coronary artery disease. Both have important implications for patient prognosis and treatment, and testing therefore appears to be warranted. On the other hand, the cost conservation movement in medicine dictates that physicians limit unnecessary, costly, possibly risky testing when the diagnostic yield is low. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 12 publications
2
15
0
5
Order By: Relevance
“…Longer follow-up periods would provide more precise estimates of 10-year cumulative risk, but our 5-year risk data provide evidence that the long-term risk of MI and vascular death is as high after ischemic stroke as the risk of coronary risk equivalents. Because survivors of ischemic stroke may be more likely to die of cardiac causes than of recurrent stroke, 19,20,21 our data reinforces the urgency of focusing on cardioprotective, as well as cerebroprotective, therapies in this patient population. Lacunar stroke patients had a lower risk of subsequent MI and vascular death in our population, although even in this lower risk group, risk approached the level of a coronary risk equivalent.…”
Section: Dhamoon Et Al Cardiovascular Risk After Strokesupporting
confidence: 66%
“…Longer follow-up periods would provide more precise estimates of 10-year cumulative risk, but our 5-year risk data provide evidence that the long-term risk of MI and vascular death is as high after ischemic stroke as the risk of coronary risk equivalents. Because survivors of ischemic stroke may be more likely to die of cardiac causes than of recurrent stroke, 19,20,21 our data reinforces the urgency of focusing on cardioprotective, as well as cerebroprotective, therapies in this patient population. Lacunar stroke patients had a lower risk of subsequent MI and vascular death in our population, although even in this lower risk group, risk approached the level of a coronary risk equivalent.…”
Section: Dhamoon Et Al Cardiovascular Risk After Strokesupporting
confidence: 66%
“…According to this hypothesis, previous reported series and clinical trials have demonstrated that patients with cerebrovascular disease are more likely to die in follow-up from cardiovascular than from cerebrovascular causes. 37,38 In this study, we have found an age-dependent increase in serum chitotriosidase activity. A similar effect of age on chitotriosidase activity has been previously described in subjects with different lysosomal disorders and in the general population.…”
Section: Discussionsupporting
confidence: 56%
“…Since it appears that polyvascular disease has a more aggressive risk profile, it is likely to require more intensive medical therapy. 3,[18][19][20] The problem posed by polyvascular disease is likely to be underestimated for several reasons. One contributing factor is the frequent underdiagnosis of PAD, 10 caused by its asymptomatic presentation in twothirds of patients.…”
Section: Discussionmentioning
confidence: 99%